Musiklyrik i läroböcker i franska för den svenska skolan - Mattias Aronsson (Dalarna university, 2021)
The article investigates song lyrics included in twelve textbooks designed for the teaching of French as a foreign language in the Swedish school system. The underlying assumption is that selections made by textbook authors are important for the canonization of literature. The analysis of what is included and what is excluded in these textbooks is highly relevant in order to understand the norms prevailing in the system of education and, consequently, in society as a whole. The corpus consists of 61 song lyrics and the results indicate that these texts partly have a conservative role, insomuch as they transmit an already canonical French cultural heritage (traditional folksongs, children's songs, and the works of a few consecrated artists in the chanson-tradition of the 1950's and 1960's) to the Swedish pupils. However, the other part of the corpus consists of more contemporary material from the decade preceding the publication of the textbooks. The corpus is male dominated (two thirds of the identified artists are men), and most of the songs (84%) deal explicitly or implicitly with Metropolitan France, with only a small percentage (16 %) representing the Francophone world outside of France. The main conclusion of the article is that the lyrics included in the textbooks consolidate rather than challenge the prevailing norms and hierarchies.